1972 - 2005: En la cuarta década de la investigación sobre grupos estrtégicos qué hemos aprendido? - J. L. Hervás Oliver; J. I. Dalmau Porta; J. Albors Garrigós (Investigaciones Europeas de Dirección y Economía de la Empresa (IEDEE), 2006)
This study show an exhaustive and current analysis about all the relevant literature on strategic groups published to date. Thus, the target is double. First, we analyse and classify the main papers in the field in order to clarify all de advantages and limitations got in the selected topic. Secondly, the work compare the state-of-the-art in Spain to the international one, from the point of view of the different stream researches, the methodology employed, the samples and the articles outcomes. Lastly, we offer a current photography and debate the future of the topic.
Keywords: 330; strategic groups; methodology; Spanish and international research gap; stateof-the-art